Governance and democracy in Asia - Inoguchi, Takashi; Carlson, Matthew (Modernity and identity in Asia series, 2006)
This book examines what citizens think about governance and democracy and the actual practices of governments in Asia, one of the most dynamic and divergent regions of the world. Using public opinion surveys and other evidence, the authors investigate such topics as government perception, human rights, democracy, and political development for a total of seven countries located in East, Southeast, and South Asiaâ€"China, India, Japan, Malaysia, South Korea, Taiwan, and Thailand. Governance and Democracy in Asia contains detailed country studies, extensive cross-country comparisons, and a wealth of new data. It will appeal to scholars and students of Asian politics, public opinion, political development, and democratization.